إشكاليات تحديد مفهوم البيئة الإعلامية في بحوث الإعلام - عبدلي، أحمد Abdeli, Ahmed; دهماني، سهيلة (جامعة زيان عاشور الجلفة, 2018)
This study aims to look for the conceptual Indigenization for the media environment and the term roots within the theoretical and sociological context This study aimed to identify the term of media environment that has emerged with the existing of the communicator studies and factors affecting his news product Identifying the educational, social, political, economic and relational atmosphere surrounding the communicator, would provide overall environmental background that determines the professional field map for journalists, "and this is called the media environment." We tried through this scientific review to focus on the the term’s dimensions and components, which consists of several factors: personal, social, cultural and its effectiveness in the practice of journalism in general, stopping at the saying of ROBERT HAREEL who think that we can not understand any press without the journalist, and this is what PIERRE BOURDIOU has advocated when he said that the meaning of very personal acts and most transparent do not belong to the person who is do them, but to the full system of relationships that occur within and through it.
تذهب هذه الدراسة للبحث عن التأصيل المفاهيمي للبيئة الإعلامية وجذور المصطلح ضمن السياق النظري والسوسيولوجي، قصد التعرف على مصطلح البيئة الإعلامية الذي ظهر مع دراسات القائم بالاتصال والعوامل المؤثرة على منتوجه الإخباري. فالتعرف على الجو التعليمي والاجتماعي والسياسي والاقتصادي والعلاقاتي الذي يحيط بالقائم بالاتصال، من شأنه أن يقدم الخلفية البيئية الشاملة التي ترسم خريطة الميدان المهني للصحفيين "وهذا ما يسمى بالبيئة الإعلامية" وحاولنا من خلال هذا الاستعراض العلمي التركيز على أبعاد ومكونات المصطلح الذي يتكون من عدت عوامل: شخصية واجتماعية وثقافية وفاعليتها في ممارسة المهنة الصحفية بشكل عام متوقفين عند طرح ROBERT HAREEL الذي أصر بالقول أنه لا يمكن لنا فهم أي صحافة دون الإنسان الذي يصنعها، وهذا ما ذهب إليه PIERRE BOURDIOU حين قال أن معنى الأفعال الشخصية جدا والأكثر شفافية ليست ملكا للفاعل الذي يقوم بها ولكن للمنظومة الكاملة للعلاقات التي تتم داخلها ومن خلالها.
Keywords: الإعلام -- البيئة الإعلامية -- البحوث الإعلامية -- القائم بالاتصال